Sustainable Tourism and Community Empowerment Through Repurposing Used Cooking Oil into Aromatic Candles - Ayu Helena Cornellia; Yedna Istiraharsi (Publikasi Indonesia, 2026)
This study examines the transformation of used cooking oil into aromatic candles as an innovative strategy to support sustainable tourism development in Ngestirejo Tourism Village, Gunungkidul, Yogyakarta. The research is motivated by environmental challenges related to improper disposal of used cooking oil and the need to develop community-based tourism products that align with circular economy principles. The objective of this study is to analyze the environmental, economic, and social impacts of repurposing used cooking oil into value-added products within a rural tourism context. This study employs a convergent mixed-methods approach, combining quantitative surveys of tourists and qualitative data from interviews, observations, and documentation involving local community members. The results show a significant improvement in environmental awareness, increasing from 30% to 78% among the community. Additionally, approximately 120 liters of used cooking oil were successfully repurposed into around 200 units of aromatic candles, contributing to waste reduction and environmental sustainability. From an economic perspective, the initiative generates additional income opportunities for local residents, while socially, it enhances community participation, empowerment, and collaborative engagement. Furthermore, tourist responses indicate high levels of satisfaction and interest in eco-friendly products, highlighting the potential of such innovations to enrich visitor experiences and strengthen destination branding. In conclusion, the Waste-to-Value approach demonstrates strong potential as a sustainable tourism strategy that integrates environmental management, community empowerment, and economic development. This study contributes theoretically to the application of circular economy concepts in community-based tourism and practically offers a replicable model for developing sustainable, small-scale tourism innovations in rural areas.